Effect of sintering temperature in argon atmosphere on microstructure and properties of 3D printed alumina ceramic cores - He Li; Yongsheng Liu; Yansong Liu; Qingfeng Zeng; Kehui Hu; Zhigang Lu; Jingjing Liang (Journal of Advanced Ceramics, 2020)
Abstract Alumina ceramics with different sintering temperatures in argon atmosphere were obtained using stereolithography-based 3D printing. The effects of sintering temperature on microstructure and physical and mechanical properties were investigated. The results show that the average particle size, shrinkage, bulk density, crystallite size, flexural strength, Vickers hardness, and nanoindentation hardness increased with the increase in sintering temperature, whereas the open porosity decreased with increasing sintering temperature. No change was observed in phase composition, chemical bond, atomic ratio, and surface roughness. For the sintered samples, the shrinkage in Z direction is much greater than that in X or Y direction. The optimum sintering temperature in argon atmosphere is 1350 °C with a shrinkage of 3.0%, 3.2%, and 5.5% in X, Y, and Z directions, respectively, flexural strength of 26.7 MPa, Vickers hardness of 198.5 HV, nanoindentation hardness of 33.1 GPa, bulk density of 2.5 g/cm3, and open porosity of 33.8%. The optimum sintering temperature was 70 °C higher than that sintering in air atmosphere when achieved the similar properties.